Neoplatonism and the philosophy of nature - Wilberding, James; Horn, Christoph (Oxford : Oxford University Press, 2012)
This volume dispels the idea that Platonism was an otherworldly enterprise which neglected thestudy of the natural world. Leading scholars examine how the Platonists of late antiquity sought to understand and explain natural phenomena: their essays offer a new understanding of the metaphysics of Platonism, and its place in the history of science.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Neoplatonism; Philosophy of nature -- History